The Influence Of Work Environment, Compensation, Workload, And Career Development On The Performance Of Nurses At Bethesda Hospital Wonosari, Special Region Of Yogyakarta In 2025 - Widyaningsih Widyaningsih; Sumijatun Sumijatun; Nurcahyo Andarusito; Thika Marliana (Journal of Ageing And Family, 2024)
The presence of nurses as human resources is a valuable asset for the sustainability of the hospital, which needs attention so they can work optimally. An initial survey at RS Bethesda Wonosari DIY found that very few nurses performed at a level categorized as competent according to the hospital's expectations. This research was conducted in December 2024, aiming to analyze the factors influencing nurse performance at RS Bethesda Wonosari DIY using a quantitative design and a cross-sectional approach. The respondents in this study are all 50 nurses. Primary data collection was conducted through the distribution of questionnaires that had been tested on 30 people at RS Panti Waluyo Solo. The univariate results show that the majority of respondents are female, have an Associate's degree in Nursing, are of productive age, and have less than 5 years of work experience. The lowest achievements obtained from the variables studied: work environment (73.5%), provision of new information (73%), performance bonuses for employees (46%), work for patient safety (79%), fully responsible nursing care (52.5%), completion of work according to targets (74.5%). Completion of work on time (76.5%) and communication with superiors (67.5%). The bivariate results show that the variables positively affecting nurse performance are workload (p: 0.002), work environment (p: 0.002), and career development (p: 0.005), each with a very weak influence, while the variable that does not have an effect is compensation (p: 0.173). The multivariate results indicate that workload, work environment, compensation, and career development collectively have a significant impact on nurse performance (p: 0.001), with the most influential factor being workload (β) 0.623 (p: 0.017). The recommendation from this study is that the workload of nurses needs to be balanced, fair, and evenly distributed to avoid fatigue, improve workspace layout, provide bonuses for outstanding nurses, increase responsibility in nursing care, and for management to allocate time for discussions with nurses regarding career development programs.